2009
DOI: 10.3899/jrheum.081096
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Pack-year History of Smoking and Response to Tumor Necrosis Factor Antagonists in Patients with Rheumatoid Arthritis

Abstract: RA patients with a history of smoking were more likely to show a poor response to TNF antagonists. Response failure was associated with the intensity of previous smoking, irrespective of smoking status at initiation of anti-TNF therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
53
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 43 publications
8
53
1
1
Order By: Relevance
“…Harty and Veale have confirmed our finding of higher tender joint counts and overall DAS scores in ever-smokers compared with never-smokers in patients with RA receiving anti-TNF therapy 1 . However, in contrast to our findings, they also suggest that ever-smokers have marginally higher mean swollen joint counts than never-smokers at both 3 and 12 months.…”
Section: To the Editorsupporting
confidence: 78%
“…Harty and Veale have confirmed our finding of higher tender joint counts and overall DAS scores in ever-smokers compared with never-smokers in patients with RA receiving anti-TNF therapy 1 . However, in contrast to our findings, they also suggest that ever-smokers have marginally higher mean swollen joint counts than never-smokers at both 3 and 12 months.…”
Section: To the Editorsupporting
confidence: 78%
“…In addition, others have reported that RAaffected male, current smokers were less likely to experience remission than their 4 never-or former-smoking counterparts, an association that was not detected in females [22]. These observations are in keeping with several reports on the negative impact of smoking on the response to tumour necrosis factor (TNF) antagonists in particular [23][24][25][26], as well as methotrexate [26], in patients with RA [23][24][25][26].…”
Section: Smoking and Rasupporting
confidence: 77%
“…A majority of studies classified smoker or non-smoker by smoking status at the time of drug initiation, but some studies considered ex-smoking status. [7,8,[10][11][12] Some studies defined the amount of smoking as more than 5 cigarettes per day within 6 months from initiation of drug administration, [16,19,20,28,29] more than 7 cigarettes per week, [18,26] more than 1 cigarette per day, [17] or the presence of smoking without considering cigarette numbers. [13][14][15][22][23][24][25]27,[31][32][33][34] These variable smoking definitions could contribute to the discrepancy in the study results.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 28 articles were finally selected. Among them, 6 articles were for RA [7][8][9][10][11][12] and 22 articles were for CD. Figure 1 shows the literature selection flows.…”
Section: Literature Selectionmentioning
confidence: 99%
See 1 more Smart Citation